The effects of Lactobacillus delbrueckii and Lactobacillus rhamnosus on cytokines and their related molecules: An ex vivo study on patients with systemic lupus erythematosus - Atefeh Alaei,; Mahmoud Mahmoudi,; Maryam Sahebari,; Zohreh Vahidi,; Nafiseh Tabasi,; Maryam Rastin, (Archives of Rheumatology, 2023)
Objectives: This study aimed to assess the ex vivo impact of Lactobacillus delbrueckii (L. delbrueckii) and Lactobacillus rhamnosus (L. rhamnosus) on inflammatory and anti-inflammatory cytokines as well as their related molecules on the peripheral blood mononuclear cells (PBMCs) of systemic lupus erythematosus (SLE) patients. Patients and methods: This study was conducted with 20 newly diagnosed SLE patients (18 females, 2 males; mean age: 33.3±12.4 years; range, 18 to 68 years) between September 2017 and September 2018. Extracted PBMCs from each patient were divided into 4 cell groups in our study. Three cell groups act as treatment groups receiving L. rhamnosus (107 CFU/mL), L. delbrueckii (105 CFU/mL) or a mixture of both, and one group act as our untreated control group in the absence of any probiotic agents. All cell groups were cultured in RPMI 1460 medium for 48 h. Then, total RNA was extracted, and cDNA was synthesized. Results: The gene expression levels of forkhead box P3 (FOXP3), transforming growth factor beta (TGF-β), interleukin (IL)-6, IL-10, and IL-2 were evaluated by a quantitative real-time polymerase chain reaction. The results revealed that expression levels of FOXP3, TGF-β, IL-10, and IL-2 increased and the level of IL-6 decreased in probiotics-receiving groups compared to the control group. Lactobacillus delbrueckii and L. rhamnosus enhanced the expression of regulatory T cell-related molecules such as FOXP3 and IL-2 and also increased the expression of IL-10. These probiotics also reduced the expression of IL-6 as proinflammatory cytokines in the PBMCs of SLE patients. Conclusion: The results of the present study show that these probiotics could be effective in regulating the balance of cytokine gene expression ex vivo , and due to their beneficial effects, they can be an intriguing option in the production of new complement drugs for SLE